Comparison of immunohematological profile between endurance- and power-oriented elite athletes - Morgado, J. P.; Matias, C. N.; Monteiro, C. P.; Alves, F.; Reis, J. F.; Santos, D. A.; Silva, A. M.; Martins, F.; Seixas, M. T.; Rocha-Pereira, P.; Sardinha, L. B.; Laires, M. J. (Applied Physiology, Nutrition, and Metabolism, 2017)
There is general perception that elite athletes are highly susceptible to changes in immunohematological profile. The objective of this study was to compare immunohematological parameters of elite athletes of different aerobic and muscular strength sports and analyze changes over 2 months. Sixteen judoists and 14 swimmers were evaluated 2 months before (M1) and immediately prior to competition (M2). Hemogram and lymphocytes subpopulations were assessed with automatic counter and flow cytometry, respectively. Judoists had higher neutrophils and lower monocytes and eosinophils percentages than swimmers at M1 and M2. At M2 judoists had lower red blood cells (RBC), hemoglobin, and hematocrit than swimmers. At M2 judoists` hematocrit and CD16 decreased while swimmers` hemoglobin and hematocrit increased. In conclusion, neither sports characteristics nor intense training seem to displace the athletes` immunohematological profile out of the clinical range, despite the possibility of occurrence of microlesions that may stimulate production of leukocytes and reduction of RBC in judoists.